Human development - Crandell, Thomas L. (McGraw Hill, 2012)
This long-trusted text features an interdisciplinary, cross-cultural, and contextual perspective on development. Applications to psychology, health care, social work, education, and family dynamics make this a perfect book for classes with a mixed population of majors